2017
DOI: 10.1002/ece3.3552
|View full text |Cite
|
Sign up to set email alerts
|

Colorful seashells: Identification of haem pathway genes associated with the synthesis of porphyrin shell color in marine snails

Abstract: Very little is known about the evolution of molluskan shell pigments, although Mollusca is a highly diverse, species rich, and ecologically important group of animals comprised of many brightly colored taxa. The marine snail genus Clanculus was chosen as an exceptional model for studying the evolution of shell color, first, because in Clanculus margaritarius and Clanculus pharaonius both shell and foot share similar colors and patterns; and second, because recent studies have identified the pigments, trochopun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…Studies have revealed that uroporphyrin pigments are responsible for coloration of shells and soft tissues in several molluscs (reviewed in Williams 2017). In scallops and marine snails, several genes related to porphyrin metabolism were differentially expressed in mantles with different colors (Ding et al 2015;Williams et al 2017), whereas for MECOM, the difference is not significant in adult mantle tissues suggesting that it may express and function during early shell formation. In this study, the QTLs related to shell coloration and growth were revealed by mapping with one bi-parental family, which represents only a small cross section of the breeding germplasm.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have revealed that uroporphyrin pigments are responsible for coloration of shells and soft tissues in several molluscs (reviewed in Williams 2017). In scallops and marine snails, several genes related to porphyrin metabolism were differentially expressed in mantles with different colors (Ding et al 2015;Williams et al 2017), whereas for MECOM, the difference is not significant in adult mantle tissues suggesting that it may express and function during early shell formation. In this study, the QTLs related to shell coloration and growth were revealed by mapping with one bi-parental family, which represents only a small cross section of the breeding germplasm.…”
Section: Discussionmentioning
confidence: 94%
“…As recently demonstrated in the case of marine snail, carboxylic acid porphyrins contribute to the pink-red and yellow-brown colours of shells 20 . These porphyrins are considered as side products of the haem biosynthetic pathway 3 . Haem is a well-known porphyrin complexed with Fe(II), able to transport oxygen indispensable for cellular aerobic respiration.…”
Section: Consist[ing] Of Radiating Sectors or Rays Of Various Widthsmentioning
confidence: 99%
“…This gap of knowledge is partly due to the lack of elucidation of the chemical nature of shell pigments, particularly in the Crassostrea genus. By combining the identification of shell pigments with corresponding biosynthetic pathways and associated genes, key information on the relation between shell colouration, mineralization or other molecular mechanisms can be obtained as previously reported in marine snails 3 . Therefore, the identification of shell pigments appears to be a possible gateway to the recovery of natural dyes from wasted oyster shells for a broad range of applications in health or material science, helping to contribute to a sustainable future for shellfish farming industry 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that the notch signalling pathway plays a vital role in shell pigmentation in the clam Meretrix meretrix , while calcium signalling may activate this pathway and influence shell colour [12]. Sequential layer-by-layer mineralisation is directed by cells of the mantle edge in Pfu ., and pigments, glycoproteins and polysaccharides in the periostracum layer are secreted by the mantle or foot tissue in molluscs [13, 14]. Thus, there may be a close relationship between biomineralisation and pigment deposition, with some genes acting as a bridge between these two biological phenomena.…”
Section: Introductionmentioning
confidence: 99%